PERBANDINGAN PENDAPATAN PETANI YANG MENGGUNAKAN METODE PERTANIAN KONVENSIONAL DAN ORGANISASI PETANI PADI - Rut Nadia Hutahaean; Dwi Pratiwi (Cahaya Ilmu Bangsa, 2024)
This research aims to compare the income of rice farmers who use conventional and organic farming methods in Indonesia, which is known as an agricultural country. Conventional farming methods, which rely on synthetic fertilizers and pesticides, offer increased crop yields in the short term, but often have negative impacts on soil and environmental quality. On the other hand, organic farming methods, which are more environmentally friendly, reduce the use of chemicals and focus on sustainable farming practices. Using survey methods and interviews with farmers, this research found that organic farmers have a higher net income than conventional farmers, even though their land productivity is lower. These results indicate that lower operational costs and higher selling prices for organic products contribute to the revenue differences. These findings are expected to provide insight for farmers and policy makers in choosing more profitable and sustainable farming methods, as well as encourage further research into the social and environmental impacts of both farming methods.